The concept of "creative thinking" as featured in the holy Qur’an التفك - Mohamed Fathy, Mohamed Abdelgelil; Munir, Al iwadhi; Muhammad Mahmud, Habib (2020)
The holy Qur'an is the source of our glory and dignity that guides people to the right way in this life. However, there are some people who used their intelligence to distort the facts for personal gain or fame, they destroyed, killed and plundered peoples' own wealth and national resources. Due to their evil deeds, they shall be remembered in a bad memory over the ages so that people draw lessons from what God punished them in this world and what awaits them in the hereafter. The goal of creative thinking is that the Qur’an and Islamic law urged people to do it. We are constantly ordained to think, meditate with so many different verse emphasizing the importance of mind to do so. Consequently, we can find that one of the most important results that the researcher came out is that the Holy Quran is meant to address the mind of the reader to think giving incentives to this matter whereby we see a whole Surah embedded in the Holy Qur'an for this purpose whether implicitly marked or explicitly mentioned both are to make us fond of using our intellect. Since our need is not limited to just a few individuals to excel in some areas of creativity, but to a creative and thoughtful people, the Qur'an brings inspiring stories of people who invoked their minds in pursuit of great achaivments, and urges us to think about them, and to confront everything that our religion and mind satisfies, operating from Islamic law coupled with rational intellectually thinking.